Actual Evapotranspiration of Unirrigated Grass in a Smart Field Lysimeter. Issue 1 (29th March 2018) - Doležal, František; Hernandez-Gomis, Rebeca; Matula, Svatopluk; Gulamov, Mukhitdin; Miháliková, Markéta; Khodjaev, Sanjar
Abstract : Core Ideas: Small smart lysimeters make high‐quality research of low and dense crops easy. FAO 56 can estimate well the reference crop ET on non‐ or mildly stressed sites. Weather station grass (not water stressed) has lower ET than the reference crop. Lysimeters are basic instruments for evapotranspiration measurement. This study characterized the actual evapotranspiration of unirrigated and unfertilized grass in a warm region of the Czech Republic on a Chernozem loamy soil. An SFL‐300 weighing lysimeter (diameter 0.3 m, depth 0.3 m) was used for this purpose. The suction at its bottom was maintained at the same level as in the native soil nearby. We selected 585 rainless days with regular records for the analysis of daily differences. On most days, the lysimeter‐measured actual evapotranspiration, ETa, was smaller than the Penman–Monteith FAO 56 reference crop evapotranspiration, ET0 . The FAO 56 procedure was found to be a reasonable estimator of the unstressed evapotranspiration in a moderately stressed environment. The ETa /ET0 ratio and the canopy surface resistance, r s, depend on the soil water content and suction measured at 5 cm. These graphs break down into horizontal unstressed parts and declining (for ETa /ET0 ) or inclining (for r s ) water‐stressed parts. The ratio ETa /ET0 is about 85% and r s is about 250 s m −1 when the grass is not under water stress. The annual curve of the unstressed crop coefficient has a sine shape. An energy balance criterion suggests that advection of heat is important in winter but not so much in summer. The study provides parameters of evapotranspiration for a canopy that can be found on many standard weather stations and demonstrates that high‐quality research into evapotranspiration of low, dense, and shallow‐rooting crops is possible with small lysimeters of this type.